Hubungan antara Prokrastinasi Kerja dengan Stres Kerja pada PNS - Permatasari, Atika Indah, Achmad Dwityanto, S.Psi, M.Si (2016)
One of human resources which is quite important to be observed for operations of Government wheels are civil servants or commonly called PNS, but when the performance of PNS is interrupted due to work stress then need to be searched the cause it. One of the factors that affect the work stress is procrastination at work. Aim to this research is to know the relationship between the procrastination at work with job stress, so the authors propose the hypothesis "there is a positive relationship between the work procrastination with job stress". Subjects in this study were PNS of Wonogiri Setda, which totaling 163 subjects. The sampling technique is a quota non random sampling namely sampling techniques, namely determine a certain amount as target that must filled within taking the sample of the population. The measure instrument which is used to reveal research variables there are 2 kinds of measure instrument, namely: (1) the scale of work procrastination, and (2) job stress scale. Data analysis in this study is uses of product- moment correlation. Based on the analysis results, so that obtained correlation between work procrastination with job stress of (r) amount of 0.507 with p = 0.000 where p < 0.01, this means there is a very significant positive relationship between work procrastination with job stress. That is, the higher the work procrastination then the higher the job stress of employee, and reverse the lower work procrastination then also the lower job stress of employees. The empirical mean of work procrastination variable is amount of 87.4 and hypothetic mean is amount of 105. It shows that empirical mean > hypothetic mean that illustrates that generally the PNS of Wonogiri Setda has a low work procrastination. Further the empirical mean of work stress variables is amount of 52.08 and hypothetic mean is amount of 60. It shows that empirical mean > hypothetic mean that illustrates that generally the PNS of Wonogiri Setda also has low work stress. The role of the work procrastination toward job stress (SE) is amount of 25.7%, that means there is still 74.3% that affect job stress, for example: environmental factors, and social factors.